Effect of mesenchymal stem cells on glial cells population in cuprizone induced demyelination model. (June 2019) - Barati, Shirin; Kashani, Iraj Ragerdi; Tahmasebi, Fatemeh; Mehrabi, Soraya; Joghataei, Mohammad Taghi
Abstract: Mesenchymal stem cells (MSCs) have a notable potential to modulate immune responses and protect the central nervous system (CNS), mostly by secreting factors that affect inflammation. MSCs have the ability to improve several autoimmune diseases in animal models including multiple sclerosis (MS). MS is a disease of the CNS among adult humans and it is characterized by demyelination, neuroinflammation and gliosis. In this study, we first induced chronic demyelination by cuprizone, followed by intraventricular injection of MSC. Our results showed that MSC significantly decreased microgliosis and astrocytosis by secreting cytokines that have neuroprotective activity including TGF-β and CX3CL1. Also, downregulation of IL-1β and TNF-α as inflammatory chemokines was seen along with decreased astrocytes and microglia activation. Finally, these results showed that trophic factors secreted by MSC can increase oligodendrocyte population and remyelination rate by reducing pro-inflammatory factors. These findings demonstrate that MSC could decrease inflammation, gliosis and demyelination with neuroprotective and immunomodulating properties in chronic cuprizone demyelination model. Therefore MSC transplantation can be considered as a suitable approach for enhancing myelination and reducing inflammation in diseases such as MS. Highlights: The cuprizone administration for 12 weeks induced chronic demyelination model. The MSCs can significantly decrease TNF-α and IL-1β. Mesenchymal stem cell transplantation significantly decreased microgliosis and astrocytosis. MSCs could significantly increased olig2 positive cells and remyelination in corpus callosum.